The Effect Of Total Quality Management (Tqm) On Operational Performance (Survey at the Rajapolah Regional Cuttlefish Company, Tasikmalaya Regency) - Rifki Redha Meyrandi; Rita Tri Yusnita; Suci Putri Lestari (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect of Total Quality Management on Operational Performance (Survey at the Rajapolah Regional Cuttlefish Company, Tasikmalaya Regency). The method used in this study is causality, with a sample of 30 respondents who are company owners, production managers and deputy production managers of 10 Cuttlefish Companies in the Rajapolah area of Tasikmalaya Regency. The analytical tool used in this research is simple regression using SPSS Version 25. Based on the calculations, it was found that the application of Total Quality Management had a positive and significant effect on the operating performance of cuttlefish companies in Rajapolah, Tasikmalaya Regency.